Eservice Quality For Customer Satisfaction Measurement: A Case Study On Islami Bank Bangladesh Ltd. - Shahabuddin , A. M. (Global Disclosure of Economics and Business, 2014)
The purpose of the study is to identify customer satisfaction through e-service quality of Islami Bank Bangladesh Limited (IBBL). Buckley (2003:455) defines e-Service as the electronic provision of a service to customers whilst Santos (2003:234) describes e-service as the provision of consumers with a superior experience with respect to the interactive flow of information. The researchers used judgment sampling. Customers faced ATM service disorder, problems in using using sms banking services, prompt service from the bank. User-friendly, responsive online service experiences, educating customer how to use online service, training of employees will increase the e-service quality of IBBL in future. JEL Classification Code: M3